(untitled) (Research, Society and Development, 2022)
This article reports on the teaching practices and academic training of students graduated in Belém do Pará, bringing reflections from the analysis of supervised internships in times of the pandemic, strongly influenced by technological development and biological warfare that plague the globalized world and that puts in guides professional training. In this perspective, the general objective of this research is to provide reflections on the challenges of doing supervised internships in the remote modality, in higher education. This is an exploratory research with a qualitative approach with a focus on Praxis, modern dialectic criticism followed by dialogue and interaction between subjects in the teaching and learning process. The theoretical framework used was based on Kosik, Gaspar, Ghedin, with the concepts of praxis activity in the internship; Andrade, on internship conceptions, concepts and definitions; and Prodanov and Freitas, on the researcher’s approach to the problem. In this study, in addition to contributing to new dialogues that involve the current social context, it is also shown that just as internship offers outside the field of activity provide opportunities for the professional growth of students, in the same way the internship opportunities in the virtual environment, also provide opportunities for their growth and tend to strengthen the integration between theory and practice.